How Developed-Country Firms Make Standardization/Transfer and Adaptations Decisions in Relation to their Developing-Host-Country Operations?. Issue 2 (3rd April 2019) - Gebrekidan, Desalegn A.; Hoc, Le Hieu; Mukhtar, Syeda-Masooda
Abstract: Factors influencing firms' standardization and adaptations decisions tend to be treated as static isolated entities in the extant literature. Further, the focus is predominantly on Western MNCs and product development or marketing functions with manufacturing firms and the emerging/developing country perspective underrepresented. We explore factors, as well as their interrelations that determine standardization and adaptations decisions when a developed country manufacturing firm establishes operations in a developing country. Purposefully, Italian manufacturing firms with operations in Vietnam are examined. We identify functions, processes, and practices that are standardized/transferred and those that are adapted. A theoretical model is developed based on the findings.